Tuberculosis transmission across three states: The story of a solid organ donor born in an endemic country, 2018. Issue 6 (8th July 2020) - Jones, Jefferson M.; Vikram, Holenarasipur R.; Lauzardo, Michael; Hill, Amy; Jones, Jeffrey; Haley, Clinton; Seaworth, Barbara; Oldham, Sara; Brown, Marcus; Gutierrez, Felipe; Basavaraju, Sridhar V.
Abstract: Transmission of tuberculosis (TB) from a deceased solid organ donor to recipients can result in severe morbidity and mortality. In 2018, four solid organ transplant recipients residing in three states but sharing a common organ donor were diagnosed with TB disease. Two recipients were hospitalized and none died. The organ donor was born in a country with a high incidence of TB and experienced 8 weeks of headache and fever prior to death, but was not tested for TB during multiple hospitalizations or prior to organ procurement. TB isolates of two organ recipients and a close contact of the donor had identical TB genotypes and closely related whole‐genome sequencing results. Donors with risk factors for TB, in particular birth or residence in countries with a higher TB incidence, should be carefully evaluated for TB.